Assessing Fatigability in Mobility‐Intact Older Adults. Issue 2 (13th January 2014) - Simonsick, Eleanor M.; Schrack, Jennifer A.; Glynn, Nancy W.; Ferrucci, Luigi
<x xml:space="preserve">Abstract</x> Objectives To evaluate the criterion validity of two measures of fatigability, defined as performance deterioration or perceived effort to perform a standardized task. Design Cross‐sectional analysis of data from the Baltimore Longitudinal Study of Aging (BLSA). Setting National Institute on Aging, Intramural Research Program, Clinical Research Unit, Baltimore, Maryland. Participants Six hundred five men (53.7%) and women aged 65 to 97 participating in the BLSA and eligible for endurance walk testing without a walking aid. Measurements Fatigability was assessed using completion status and lap times from a 400‐m walk performed "as quickly as possible" and perceived exertion rating using the Borg scale (range 6–20) after 5 minutes of treadmill walking at 1.5 miles per hour (0.67 m/s). Criterion measures included self‐report of tiredness, level of weakness and energy in past month, and walking ability and objective measures of usual and fast gait speed, time to complete 10 chair stands, and grip strength. Covariates included age, race, sex, obesity, smoking status, and walking activity. Results Of mobility‐intact older persons, 23% exhibited performance deterioration (slowed or stopped) during the 400‐m walk, and one‐third reported more than very light exertion after a 5‐minute slow walk. Slowing was strongly associated with self‐reported fatigue and walking ability but weakly associated with performance‐based mobility measures. High perceived exertion was associated with tiredness, weakness, and reported and observed mobility deficits. Conclusion Slowing down may have low sensitivity for identifying fatigability in older persons, but ascertaining perceived exertion during a defined workload shows promise. In seemingly healthy, motivated individuals, fatigue and fatigability were common and may affect socially meaningful mobility behaviors. Assessment of fatigability in well‐elderly examinations may help identify threats to independent functioning earlier in the decline process.